Synthesis of hydroxyapatite from limestone by using precipitation method. (February 2020) - Sirait, M; Sinulingga, K; Siregar, N; Siregar, R S D
Abstract: Hydroxyapatite from limestone was synthesized by precipitation method. During the synthesization, the temperature of a 200 mesh sample was increased to 600°C for 3 hours. It was transformed CaCO3 into CaO powder. Then the CaO powder was dissolved with water to get Ca(OH)2, then it dissolved with H3 PO4 0.3M as a source of phosphate. The solution was mixed by using magnetic stirrer with a speed of 300 rpm for 1 hour. Then NH4 OH 1M solution was periodically dropped to that the solution until it became an alkaline with pH 10. The solution was stood for 24 hours and the precipitate was dried by using an oven in 120°C for 5 hours. Hydroxyapatite powder obtained was characterized by FTIR to see the major functional groups that are formed in hydroxyapatite limestone. The results obtained were 3 functional major groups that are phosphate (PO4 3− ), carbonate (CO3 2− ) and hydroxyl (OH − ) on hydroxyapatite limestone.